PSYCHOLOGICAL DEMANDS, CONTROL AND SOCIAL SUPPORT IN THE WORK OF COMMUNITY HEALTH AGENTS - Gilmara Aparecida Batista Fernandes; Angélica da Conceição Oliveira Coelho; Heloisa Campos Paschoalin; Leila Maria Mansano Sarquis; Rosângela Maria Greco (Universidade Federal do Paraná, 2018)
Objective: To identify the psychological demands, control and social support in the work of Community Health Agents. Method: Descriptive study, with a quantitative approach, carried out with 212 primary health care workers from a municipality in the interior of Minas Gerais. Data was collected between July and October 2015 from Community Health Agents of Primary Health Care units. Sociodemographic and labor characteristics were the independent variables and short scale Demand-Control Model and social support at work were the dependent variables. Results: Female working-age population. Passive job and high demand were prevalent, indicating high risk of development of psychosocial stress at work. Conclusion: Interventions in living and working conditions are necessary, especially regarding psychosocial and organizational aspects.